Domesticating the market: moral exchange and the sharing economy. (16th February 2018) - Fitzmaurice, Connor J; Ladegaard, Isak; Attwood-Charles, William; Cansoy, Mehmet; Carfagna, Lindsey B; Schor, Juliet B; Wengronowitz, Robert
Abstract: The 'sharing economy' is a contested realm, with critics arguing it represents a further development of neoliberalism, as platforms such as Airbnb and TaskRabbit, monetize previously uncommodified realms of life via renting of bedrooms, possessions, space and labor time. To date, this debate has largely ignored participants' views. Using data from 120 in-depth interviews with providers in two for-profit and three not-for-profit sites, we find that most see the sharing economy differently, as an opportunity to build a radically different market, from the bottom up. Like the detractors, they are critical of dominant market arrangements, however, they believe the sharing sector can construct personalized exchanges that are morally attuned, based on ideals of community, and that help them achieve creative and financial autonomy in their working lives. These aspirations represent an attempt to tame, or domesticate the neoliberal market.